Vocational training in Lithuania in the first half of 19th century - Endzinas, A. (Psichologija, 1962)
After the third division of the Lithuanian-Poland state in 1795, a major part of Lithuania’s lands became the property of the serfdom Russia. Annexing of Lithuania to the Russian market boosted the development of trade-economic relations. Economic relations fostered the disintegration of the feudal regime and formation of capitalist relations in Lithuania. Due to the developing economic relations, in XVIII century and at the beginning of 19th century Lithuania saw a constant increase in technical processing of agriculture production associated with the agricultural progress. Thus, the development of production or the progress of science, technology, agriculture, transport and the economics of the whole country increased the demand for professions and requires relevant qualified and supplementary workforce possessing certain knowledge and work skills. The demand for supplementary workforce was satisfied by peasants-serfs and very well-paid craftsmen mainly brought from abroad. Preparation of local specialists was lagging behind. The newcomer masters looked down on the local population and reluctantly taught them or refused to teach them at all. Therefore, training of qualified workforce for the developing industry, agriculture, and construction of water and land ways of communication and cities could be only implemented in education institutions in three ways by: 1) Organizing in Vilnius High School vocational departments to train specialists. 2) Opening new type special purpose educational institutions and courses. 3) Restructuring the comprehensive education schools into such institutions which would include applied subjects in their syllabus. Such progress of vocational education was stimulated by the traditions inherited from Educational Commission schools, the activity of the reorganized Vilnius University and its wide network of comprehensive education institutions and specialized schools operating under them, as well as the exceptional conditions in Vilnius Education Department. Special attention was paid to training practical professional skills. It was taken into account that basic comprehensive education subjects served as a basis for teaching vocational skills. Having suppressed the uprising of 1832, Vilnius University and specialized education institutions operating at it were closed, Vilnius Education Department was liquidated and specialized applied subjects eliminated from comprehensive schools’ curricula. After the uprising, reactionary provisions issued in 1828 became effective in Vilnius Education Department, according to which two educational systems based on estate were introduced. Vocational training of professionals for the state needs was implemented in three directions: 1) Vocational agricultural education institutions for training agriculture specialists were being founded 2) Vocational education institutions and training courses for vocational training were designated 3) Crafts and handicrafts trainings were carried out in specially designated educational institutions, classes and special workshops